Immunomodulatory Effect of Ethyl Acetate Extract of Permot (Passiflora Foetida L.) Leaf against the Secretion of Antibody and Delayed Type Hypersensitivity in Vivo - Andi Emelda (Journal of Global Pharma Technology, 2018)
The aim of this study was to investigate the immunomodulatory effect of ethyl acetate of extract of Passiflora foetida L leaves (EAEPL) on hypersensitivity response and antibody titer of immune cells. Hypersensitivity response test evaluated the swelling of the feet of mice, while antibody titer test evaluated the hemagglutination. Examination of antibody titer was performed in 5 groups of 25 wistar rats. All the test animals, except control group, induced by SRBC on the 3rd day intraperitoneally. The extract was given for 7 days. The hypersensitivity response test was performed in 5 groups of 25 mice (Balb/c). The groups, except control group, were given antigen (SRBC) on the 3rd day intraperitoneally and on the 7th day were administered intraplantarly. The thickness of the soles of the feet was measured using a plethysmometer before and after injecting the antigen at T4, T24 and T48. The data were processed statistically by Kruskal-Wallis then advanced test by Mann-Whitney. The group of negative control against the groups of EAEPL was significantly different (p<0.05). The antibody titer of the groups given the extract were higher than the antigen-induced group without the administration of the extract. The results show that the groups of EAEPL can increase antibody secretion. The test of hypersensitivity response showed that the group of negative control to EAEPL groups showed significantly different (p<0.05). The results showed that the swelling of the feet of mice decrease at T48. This research concludes that ethyl acetate extract of EAEPL has the immunostimulatory effect.